2017
DOI: 10.5812/ircmj.41644
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors of Hepatitis E in Eastern Iran

Abstract: Background: Hepatitis E infection is one of the most common causes of acute hepatitis. It is caused by the RNA virus of the hepatomegaly viridae family, which is transferred through stool in contaminated water. Cases of infection are most prevalent in developing countries. Objectives: This study was conducted to investigate the seroprevalence of hepatitis E among urban adults. The reason was the current lack of information on the hepatitis E prevalence among the general population in the city of Birjand in eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This implies that the aboriginals have a higher seroprevalence of anti‐HEV than the urban Malaysian population. Increasing prevalence of HEV with increasing age has reported in many studies across worldwide (Azarkar, Ebrahimzadeh, Sharifzadeh, Ziaee, & Fereidouni, ; Bricks et al, ; van Gageldonk‐Lafeber et al, ). However, age‐specific prevalence of HEV in Malaysia from both the previous study (Seow et al, ) as well as the current study could not be established due to small sample size.…”
Section: Discussionmentioning
confidence: 96%
“…This implies that the aboriginals have a higher seroprevalence of anti‐HEV than the urban Malaysian population. Increasing prevalence of HEV with increasing age has reported in many studies across worldwide (Azarkar, Ebrahimzadeh, Sharifzadeh, Ziaee, & Fereidouni, ; Bricks et al, ; van Gageldonk‐Lafeber et al, ). However, age‐specific prevalence of HEV in Malaysia from both the previous study (Seow et al, ) as well as the current study could not be established due to small sample size.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the prevalence of HEV in women residing in Birjand who were in their reproductive age was 11.7%. Having compared the results of the study with previous studies conducted in this region, it was observed that the prevalence of hepatitis E was lower in women of reproductive age than in the general population (25%) (5).…”
Section: Discussionmentioning
confidence: 90%
“…In the general population, the prevalence of hepatitis E is different across various parts of Iran. Specifically, it was 9.3% in Nahavand, 8.1% in Isfahan, 7.3% in Sari, 7.9% -15% in Tehran, and 46.1% in Ahvaz (5). In a study conducted by Jahanbakhsh et al, the prevalence of HEV was 24.37% (6).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation